Intercellular adhesion molecule 1 (ICAM-1) has a central role in cell-cell contact-mediated immune mechanisms. - Boyd, A W (1988)
The role of intercellular adhesion molecule 1 (ICAM-1) in immune function was probed by using the Wehi-CAM-1 (W-CAM-1) monoclonal antibody. This antibody blocks aggregation of cell lines mediated by the ICAM-1 molecule and is here shown to block homotypic binding of purified populations of activated T and B lymphocytes (blasts) and also aggregation of mixed T- and B-cell blasts. We also demonstrate that W-CAM-1 inhibited T-cell adhesion to normal human endothelial cells, the first step in lymphocyte egress into the tissues. In tests of immune function, W-CAM-1 had a modest inhibitory effect on T- and B-cell activation by potent mitogens and no effect on the response of activated lymphocytes to lymphokines. By contrast, activation induced by cell-cell contact (mixed lymphocyte reaction, T-cell-mediated B-cell activation) was significantly inhibited. Moreover, the antibody was shown to block elements of both effector arms of the immune system (cytotoxic cell function and immunoglobulin production). These findings show that the ICAM-1 molecule is a central component of the mechanism of lymphocyte-endothelial cell adhesion. The studies of lymphoid function demonstrate a pivotal role for this molecule in both the T-cell/T-cell and T-cell/B-cell interactions, which underpin the regulation of the immune response, and in the mechanism of cell-mediated cytotoxicity.